The prevalence of antiphospholipid antibodies in women with late pregnancy complications and low‐risk for chromosomal abnormalities. (21st September 2020) - Foddai, Silvia G.; Radin, Massimo; Cecchi, Irene; Gaito, Silvia; Orpheu, Giulia; Rubini, Elena; Barinotti, Alice; Menegatti, Elisa; Mengozzi, Giulio; Roccatello, Dario; Manetta, Tilde; Donati Marello, Barbara; et al.
Abstract: Background: Antiphospholipid antibodies (aPL) are known to increase the risk of obstetrical complications. However, aPL significance and prevalence in women with late‐onset pregnancy complications (LO‐PC) need further clarification. Objectives: To investigate the prevalence of aPL in a cohort of women who experienced LO‐PC and to compare it with a cohort of uneventful pregnancies. Methods: One hundred pregnant women who experienced LO‐PC, had a low risk for chromosomal abnormalities, and absence of fetal abnormalities were recruited from August 2018 to August 2019. One hundred women with uneventful pregnancy were included as controls. aPL testing was performed on serum samples derived from prenatal screening test and included both criteria and "extra criteria" aPL. Results: Patients with LO‐PC had significantly higher aPL prevalence when compared with controls (31/100 [31%] vs 10/100 [10%]; P < .001). More in detail, up to 26% of women with LO‐PC were positive for one aPL, with an overall prevalence significantly higher than controls (26% vs 9%; P < .05). Among single aPL positivity, patients had significantly higher rate of positivity and titers of anticardiolipin IgG (10% vs 2%; mean ± standard deviation 11 ± 13 vs 4 ± 9.6 chemoluminescent unit; P < .05) and phosphatidylserine–prothrombin antibodies (aPS/PT) IgM (15% vs 6%; mean ± standard deviation 10.2 ± 21.7 vs 3.7 ± 13.7 U; P < .05). Testing for aPS/PT (IgM/IgG) alone allowed the identification of 17 patients negative for criteria aPL. aPL‐positive patients had a significantly higher risk of preterm birth (34‐36 + 6 weeks; 10% vs 8%; P < .012). Conclusions: We report a high prevalence of aPL in our cohort. Testing for both criteria and "extra criteria" aPL in women with previous LO‐PC could improve the diagnostic accuracy identifying women at higher risk for recurrent pregnancy complications.